Cityscapes and perceptual dialectology : global perspectives on non-linguists' knowledge of the dialect landscape - Cramer, Jennifer; Montgomery, Chris (Linguist) (Language and Social Life., 2016)
While connections between language and place have been central to traditional dialectology, the perceptions non-linguists have about such connections have often been ignored. In this book the non-linguist's view is seen as central to understanding linguistic variation in and of cities. This collection of state-of-the-art Perceptual Dialectology research assesses how the urban setting influences those perceptions.